2019
DOI: 10.1111/jpc.14602
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis at a specialist paediatric centre: The electronic medical record helps to evaluate low‐value care

Abstract: Aim Low‐value care (LVC) is common. We aimed, using infants presenting to a major tertiary paediatric hospital with bronchiolitis between April 2016 and July 2018, to: (i) assess rates of chest X‐ray (CXR) and medication use; (ii) identify associated factors; and (iii) measure the harm of not performing these practices. Methods We extracted data from the electronic medical record for all children aged 1–12 months given a diagnosis of bronchiolitis in the emergency department. Factors potentially associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The impact of patient characteristics or seasonal factors on rates of CXR in bronchiolitis have not been reported. Our previous study shows males present to hospital with bronchiolitis more frequently than females, suggesting sex differences in illness presentation 18 . Younger children are often considered more vulnerable and are likely to attract more clinical concern.…”
Section: What Is Already Known On This Topicmentioning
confidence: 93%
See 4 more Smart Citations
“…The impact of patient characteristics or seasonal factors on rates of CXR in bronchiolitis have not been reported. Our previous study shows males present to hospital with bronchiolitis more frequently than females, suggesting sex differences in illness presentation 18 . Younger children are often considered more vulnerable and are likely to attract more clinical concern.…”
Section: What Is Already Known On This Topicmentioning
confidence: 93%
“…4,18 Our earlier study showed that almost 40% of children admitted to the General Medical ward receive a CXR, compared to 3% of those who are discharged home from ED. 18 The impact of patient characteristics or seasonal factors on rates of CXR in bronchiolitis have not been reported. Our previous study shows males present to hospital with bronchiolitis more frequently than females, suggesting sex differences in illness presentation.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 3 more Smart Citations